A virtual reality-based mind–body approach to downregulate psychophysiological arousal in adolescent insomnia. (June 2022) - de Zambotti, Massimiliano; Yuksel, Dilara; Kiss, Orsolya; Barresi, Giacinto; Arra, Nicole; Volpe, Laila; King, Christopher; Baker, Fiona C
Objective: In this study, we describe the rationale, supported by preliminary data, for a novel, digital, immersive virtual reality (VR)-based mind–body approach, designed to reduce bedtime arousal in adolescents with insomnia. Methods: Fifty-two high-school students (16–20 years; 32 female) with ( N  = 18) and without ( N  = 34) DSM-5 insomnia symptoms engaged with 20 min of immersive VR-guided meditation and paced breathing (0.1 Hz) ( intervention condition ) and 20 min of quiet activity ( control condition ), right before bedtime, on two separate evenings. Results: The intervention resulted in acute autonomic and cortical modulation ( p  < 0.05), leading to reduced physiological arousal (↓heart rate, ↓cortisol) compared with the control condition, with similar effects in adolescents with and without insomnia. No significant changes were detected for cognitive arousal levels. During the intervention, all participants were able to achieve the targeted 0.1 Hz breathing rate, and the majority experienced no discomfort associated with the VR exposure. However, 30–40% of the participants experienced some trouble slowing down their breathing. Conclusions: The study provides supporting preliminary evidence for the mechanism behind a novel VR-based digital approach, designed to regulate psychophysiological arousal levels by acting on neurocognitive and autonomic pathways. Further studies (e.g. randomized clinical trials) are needed to evaluate the isolated and synergistic effects of its components (e.g. VR vs. VR + paced breathing), and its efficacy, acceptance, and feasibility in alleviating insomnia symptoms in adolescents.